The supernatural society eaudiobook - Ogle, Rex (The Supernatural Society, 2022)
"Monsters have never been so much fun." –Stuart Gibbs, New York Times bestselling author of the Spy School series "Frightening and fun!" –Neil Patrick Harris, New York Times bestselling author of The Magic Misfits Readers will be scared silly in this spooky and hilarious middle grade series starter about a town chock-full of monsters and the kids who must unravel centuries of secrets to save it . Will Hunter thought his life couldn't get any worse: His parents just got divorced, His best (and only) friend now is his dog, Fitz, And his mom moved them from New York City to the middle-of-nowhere town called East Emerson. But Will was wrong—things are about to get way worse. Because East Emerson is filled with a whole lot of monsters, and he's the only person who can see them. When all the town pets (including Fitz) go missing, Will suspects there's something sinister going on. So he joins forces with outcast Ivy and super-smart Linus to uncover the ancient secrets of East Emerson. Besides, nothing bad could happen when three sixth graders team up against monsters, magic, myths, and mad science . . . right? Read all the books in The Supernatural Society series! The Supernatural Society Curse of the Werewolves